2014
DOI: 10.1016/j.neurobiolaging.2013.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and motor aging in female chimpanzees

Abstract: We present the first longitudinal data on cognitive and motor aging in the chimpanzee (Pan troglodytes). Thirty-eight adult female chimpanzees (10–54 years old) were studied. The apes were tested longitudinally for 3 years in a modified Primate Cognition Test Battery (Herrmann et al., 2007, Science 317,1360–1366), which comprised 12 tests of physical and social cognition. The chimpanzees were also administered a fine motor task requiring them to remove a steel nut from rods of various complexity. There was lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 61 publications
4
56
7
Order By: Relevance
“…If this does not occur, then such individuals are extremely unlikely to master the skill later in life (Biro et al 2003). This enhanced early-life sensitivity to social information is further evidenced by Lacreuse et al’s (2014) finding that older female chimpanzees perform worse on social cognition tasks than younger individuals. Whether wild chimpanzees acquire the bulk of their cultural repertoire during this early juvenile period, or if it only affects the acquisition of highly technical skills, such as nut-cracking (just as humans ‘grow out of’ being able to learn a language with ease), remains unclear.…”
Section: Introductionmentioning
confidence: 62%
“…If this does not occur, then such individuals are extremely unlikely to master the skill later in life (Biro et al 2003). This enhanced early-life sensitivity to social information is further evidenced by Lacreuse et al’s (2014) finding that older female chimpanzees perform worse on social cognition tasks than younger individuals. Whether wild chimpanzees acquire the bulk of their cultural repertoire during this early juvenile period, or if it only affects the acquisition of highly technical skills, such as nut-cracking (just as humans ‘grow out of’ being able to learn a language with ease), remains unclear.…”
Section: Introductionmentioning
confidence: 62%
“…The first, and only, longitudinal data obtained regarding ape cognitive and motor aging utilized a sample of female chimpanzees [Lacreuse et al, 2013]. Over a span of three years, there were no clear differences in performance, which was unexpected given the robust motor slowing findings in previous monkey and human studies.…”
Section: Discussionmentioning
confidence: 92%
“…Over a span of three years, there were no clear differences in performance, which was unexpected given the robust motor slowing findings in previous monkey and human studies. One potential hypothesis was that deficits commonly seen in aging may be due to a physical impairment unrelated to the brain (i.e., arthritis) rather than changes in the motor region of the brain [Lacreuse et al, 2013]. Hopefully, future studies that are able to combine behavioral data with structural changes in the brain can help disentangle such hypotheses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential role of progesterone in modulating cognitive function has often been disregarded (Barros et al, in press), but preliminary, albeit indirect evidence suggests that progesterone, in addition to E2, may be a significant modulator of cognitive function in cycling females. For example, Lacreuse and collaborators reported better spatial-DRST performance in long-term ovariectomized (OVX) female rhesus monkeys relative to age-matched intact females (Lacreuse et al, 2000), and found a similar spatial memory advantage in non-cycling females over cycling female in chimpanzees, independent of age (Lacreuse et al, 2014b). The lack of sex hormone quantification in these studies prevents from drawing definitive conclusions about the hormonal basis of these differences.…”
Section: Accepted Manuscriptmentioning
confidence: 97%